Perkembangan Lagu Indonesia Raya (Tahun 1928-2009) - Febriansyah Pratama Putra; Fajriudin Fajriudin; Agus Permana (UIN Sunan Gunung Djati Bandung, 2020)
The Indonesia Raya song is the National Anthem of the Republic of Indonesia, which was created by Wage Rudolf Supratman and is the only song among his many songs that is used as the national anthem. This song was first introduced to the public on October 28, 1928 as a struggle song to unite the nation. The meaning contained in the lyrics of the song is very deep and the melody is made very lively when the song is played. In its development, this song was also sung on various occasions, including when birthdays or weddings with different versions. This happens because there is no mutual agreement in the lyrics and arrangements of the song Indonesia Raya. For this reason, it is necessary to conduct research on the development of the Indonesia Raya Song from 1928 to 2009.